Seroprevalence of Trypanosoma cruzi in pregnant women in Midwest Brazil: an evaluation of congenital transmission - Nobre, Tayane (2021)
Chagas disease (CD) is caused by the protozoan Trypanosoma cruzi and it is mainly acquired through the vector route, however, blood transfusion and congenital transmission are implicated in the spread of the illness worldwide. The congenital route can occur at any stage of pregnancy and its frequency varies. In the Federal District, in Brazil, the frequency of T. cruzi infection in pregnant women and their offspring has not been updated. Thus, the aim of this study was to estimate the prevalence of T. cruzi infection in pregnant women and the rate of congenital transmission in the Federal District. A cross-sectional study was conducted to estimate the seroprevalence of T. cruzi from 2014 to 2016 in the population of pregnant women attended by the public health service throughout the Federal District and a descriptive cohort for the evaluation of congenital transmission. During the study, prenatal data of 98,895 women were consulted and pregnant women registered in 2016, presenting with positive T. cruzi serology, were part of the descriptive cohort. The estimated prevalence of T. cruzi infection in the three years was 0.19% and the congenital transmission rate was 1/40 (2.5%). Our results have shown that, although the main routes of transmission of CD have been interrupted, there is still a risk of congenital transmission in the Federal District. This present study highlights the need for the continuous implementation of a screening program for pregnant women and timely treatment of infected newborns and children.